Pengembangan Sistem Informasi Cuti pada Balai Penelitian Tanaman Pemanis dan Serat (BALITTAS) Malang berbasis Website - Nyamik Anggela Novialeta; Denny Sagita Rusdianto; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Research Institute for Sweeteners and Fibers (BALITTAS) is one of the technical implementing units (UPT) of the Agricultural Research and Development Agency which is directly responsible to the Plantation Research and Development Center in Bogor. The Research Institute for Sweeteners and Fibers (BALITTAS) has quite a lot of human resources. Leave management is still carried out using recordings in the general ledger. The leave application process uses a form obtained by the employee from the admin. The formula will be approved by the direct supervisor, the head of the administrative subdivision, and the head of the hall which will then be handed back to the admin. Manually managing data using a ledger is also at risk of being damaged and lost. Management of leave information system (SICUTI) which was developed to assist employees in the process of asking questions and obtaining information related to leave allowances. This system provides a forum for admins to manage employee data and submit leave data. The development of this system uses the waterfall model. The implementation system uses the PHP programming language and the CodeIgniter framework. The tests used are unit testing, integration testing and validation testing. Compatibility testing is carried out to determine the ability of the system to run in several browsers such as IE, Edge, Firefox, Safari, Opera, Chrome, iOS and Android. The result of this research is a website-based Leave Information System (SICUTI).